DOES YOUNG MUSLIMAH RELIGIOSITY REALLY SERVE A MODERATOR BETWEEN LIFESTYLE, MOTIVATION, AND PURCHASE DECISION? - Bachri, Naufal (CV. Radja Publika, 2021)
This research examined the influence of lifestyle and consumer motivation on purchase decision for halal skincare products and to know whether the young Muslimah religiosity moderated the lifestyle and consumer motivation effects on purchase decision or not. This study used primary data taken by distributing questionnaires to 305 respondents and by using a purposive sampling technique. The method of data analysis was Moderated Regression Analysis. The results indicated that the lifestyle and consumer motivation significantly influenced purchase decision for halal skincare products and the young Muslimah religiosity could moderate the effect of lifestyle and consumer motivation on purchase decision. This research can be meaningful for universities to develop curricula for marketing management, lecturers to develop teaching materials, students as references, and skincare companies to improve policies to increase customer satisfaction and expand the market. The purchase decision model for halal skincare products with young Muslimah religiosity as a moderator has been presented comprehensively and completely.